Characterisation of two unusual cases of haemoglobin Bart’s hydrops foetalis caused by –SEA and large novel α-globin gene cluster deletions - Wang, Yunan; Xiong, Ying; Liu, Chang; Lu, Jian; Wang, Jicheng; Qin, DanQing; Liu, Ling; Wu, Jing; Zhao, Xin; Fang, Liyuan; Du, Li; Yin, Aihua (Journal of international medical research, 2021)
Background We describe 2 unusual haemoglobin (Hb) Bart’s hydrops cases that could not be explained by traditional factors. Case presentation: Two families with a diagnosis or history of foetal hydrops were enrolled. A suspension-array system was used to detect the 23 most frequent mutations in southern China. Multiplex ligation-dependent probe amplification (MLPA) was used to screen for possible deletions. Precise characterisation of the breakpoints of the novel variants and uniparental disomy analysis were performed using a single nucleotide polymorphism (SNP) array. Quantitative fluorescence PCR was used to eliminate maternal cell contamination and nonpaternity. In case 1, the suspension-array system indicated a maternal heterozygous (–SEA/) deletion, and the paternal sample was negative. The foetal hydrops was caused by the maternal (–SEA/) deletion and a de novo α-globin gene deletion (–193). In case 2, the paternal sample had a heterozygous (–SEA/) deletion, and MLPA and SNP array analysis revealed a large maternal deletion (–227) that encompassed the α-globin gene, which explained the history of Hb Bart’s foetal hydrops. Conclusions Our cases describe 2 new α0-thalassaemia deletions and illustrate the importance of using a combination of methods to detect rare types of α-thalassaemia.